VALIDATION OF LEARNING OUTCOMES GAINED OUTSIDE ACADEMIA: A LITHUANIAN CASE OF PORTFOLIO TRAINING - Burkšaitienė, Nijolė; Šliogerienė, Jolita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article reports the results of the investigation into adults’ views of the portfolio training provided to them by a university before validation of their non-formal and informal learning. This is a mixed-method investigation conducted with the participation of 70 adults with the main aim to establish effectiveness and usefulness of the portfolio training from the adults’ perspective. The research results showed that the training was effective and useful. The participants considered that due to the training their CV writing skills improved, the awareness of the process of validation of non-formal and informal learning and of the participation requirements increased, as well as the ability to develop one’s portfolio of non-formal and informal learning was developed.The results of the participants’ feedback responses revealed five major categories of usefulness, including relevant information, abilities developed during the training, new knowledge gained during the training, the use of metacognitive strategies, and practical value of the training.The research contributes to the literature in that it increases our understanding of what adults view as relevant with regard to institution-provided support before the validation procedure of their non-formal and informal learning, which may lead to a better mutual understanding and result in adult success.